PEMIKIRAN GENDER DAN PEMBAHARUAN ISLAM: SEBUAH PENGAYAAN INTELEKTUAL ASMA BARLAS - Rifaldi Busura, Mohamad; Muzammil, Shofiyullah (Sanjiwani: Jurnal Filsafat, 2024)
The aim of this research is to elaborate on a perspective regarding gender and the reform of Islam initiated by Asma Barlas. Barlas's argument in the context of gender thinking within the Islamic reformation stems from the reality that women, in 'Arab' society, often face discrimination and marginalization. For instance, historically, Arab culture suppressed views of injustice toward the position of women. Before the advent of Islam, women in Arab society experienced discrimination and unfair treatment. During the Jahiliyah era, women were considered beings of very low status and had no role in their own lives. Their authority was held by their father and brothers before marriage, and by their husbands after marriage. Women often received inhumane treatment during that time. This study concludes that in the context of Islamic reform, Barlas's gender thinking provides a foundation for the Islamic feminist movement. By detailing the history of oppression against women and offering a more inclusive interpretation of Islamic teachings, Barlas inspires Muslim women to take an active role in advocating for their rights. Her thoughts create momentum for change in how society perceives and values women's contributions in various aspects of life.